2013
DOI: 10.7580/kjlm.2013.37.4.198
|View full text |Cite
|
Sign up to set email alerts
|

The Statistical Analysis on Legal Autopsy Performed in Korea during 2012 Year

Abstract: This statistical analysis of 4,709 legal autopsies performed in Korea in 2012 was conducted to obtain primary data about and related variables. The analysis revealed the following:1. Of the total number of deaths, men accounted for and women, 26.8%. Evidently, the number of deaths among men was more than twice that among women. 2. With respect to mode of death, 54.8% were recorded as unnatural deaths, 39.2% were natural deaths, and 6.0% had unknown causes. Of the 2,581 unnatural deaths, 44.8% were accidental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 3 publications
(1 reference statement)
0
7
0
5
Order By: Relevance
“…In Korea, hanging was the most common method of suicide for both males and females. Poisoning, drowning, falling, and sharp force injury came next [3][4][5]. The blunt force injury was the most uncommon cause among the methods of suicide.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In Korea, hanging was the most common method of suicide for both males and females. Poisoning, drowning, falling, and sharp force injury came next [3][4][5]. The blunt force injury was the most uncommon cause among the methods of suicide.…”
Section: Discussionmentioning
confidence: 96%
“…The blunt force injury was the most uncommon cause among the methods of suicide. Of those, only two cases were confirmed to have blunt head trauma as the singular cause of death [4,5].…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, future studies that use other methods of blood pressure measurement are needed to validate the findings of this study, particularly since white coat hypertension has been reported to be prevalent among young adults. 34 Second, the operational definition of CVD may be prone to misdiagnosis, as evidenced by the unusually higher rate of CHD compared with stroke among men and the low autopsy rate (1.9% of all deaths according to a report in 2013 35 ) in South Korea. Although the operational definition of CVD used in this study has been adopted from multiple previous studies using the same data source, 17,18 future studies that use a more accurate definition of CVD are needed to validate these findings.…”
Section: Limitationsmentioning
confidence: 99%
“…๊ทผ์—๋Š” ์ •๊ธฐ์ ์œผ๋กœ ๊ตญ๋ฆฝ๊ณผํ•™์ˆ˜์‚ฌ์—ฐ๊ตฌ์›์—์„œ ๋งค๋…„ ์ „๊ตญ์ ์ธ ๋ฒ•์˜๋ถ€๊ฒ€์— ๋Œ€ํ•œ ํ†ต๊ณ„์ž๋ฃŒ๋ฅผ ๋ฐœํ‘œํ•˜๊ณ  ์žˆ๋‹ค [6][7][8][9]. ํ•˜์ง€๋งŒ ์ „ ๊ตญ ๋ฒ•์˜๋ถ€๊ฒ€์— ๋Œ€ํ•œ ์ด ์ง‘๊ณ„์ž๋ฃŒ๋กœ ์ œ์‹œ๋˜์–ด, ์ง€์—ญ์˜ ํŠน์„ฑ ๋ฐ ์ธ๊ตฌ๊ตฌ์กฐ์˜ ์ฐจ์ด์— ๋”ฐ๋ฅธ ์ง€์—ญ๋ณ„ ๋น„๊ต์— ์–ด๋ ค์›€์ด ์žˆ๋‹ค.…”
unclassified